Relationship between impaired cerebral lymphatic function and iron deposition, blood flow in VaD: a clinical MRI study - Lu, Yingqi; Liu, Yushuang; Zhang, Haoran; Wu, Huixing; Long, Yuan; Pang, Cong; Xi, Juncheng; Zhang, Zhongling; Xu, Jinping; Chen, Shangjie (Frontiers in Neuroscience, 2025)
BackgroundThe neural mechanisms induced by cerebral small vessel disease (CSVD) in the vascular dementia (VaD) is extremely complex. Recent studies have identified altered lymphatic function as a key factor contributing to the development of cognitive deficits, whether they linked to iron deposition and reduced cerebral blood flow remains unclear.MethodsThe study involved 59 participants, comprising 30 healthy controls and 29 patients with VaD. Each participant underwent QSM, ASL, and DTI imaging scans and clinical measurements. The ALPS index based on DTI, QSM, and ASL for the left and right hemispheres, as well as for the whole brain were calculated and compared between groups. Regional mean susceptibility and mean CBF based on AAL template were calculated and compared between groups. Correlation analyses were performed between altered indexes and clinical measurements. Finally, mediation analyses were conducted to determine whether the mean susceptibility rate and mean CBF were involved in the modulation process of the ALPS.ResultsDTI-ALPS based analysis demonstrated a significantly lower ALPS index for the left, right, and whole brain in the VaD as compared to healthy controls. Mean susceptibility in the bilateral superior occipital gyrus and bilateral middle occipital gyrus was significantly higher, whereas mean CBF in the eft inferior frontal gyrus, opercular part, right rolandic operculum, right insula, and right heschl gyrus was significantly lower in the VaD. Further correlation analyses revealed associations between elevated mean susceptibility, reduced ALPS index, and cognitive impairments. Additionally, the results of correlation and mediation analyses suggested that CBF may be involved in the regulatory process of DTI-ALPS.ConclusionOur results demonstrated that altered lymphatic function is a key pathological factor in VaD, and reduced cerebral blood flow may play a role in this process. These findings provide a theoretical basis for identifying new targets in the treatment of VaD.